Immunobiology and Molecular Approaches to Myasthenic Crisis in the Context of Tropical Biology - Ningsih, Nur Aulia Ahya; Rifki, Muhammad; Firdaus, Nadine Aisyah Sultan; Latifa, Nindy Citra; Fathana, Prima Belia (Jurnal Biologi Tropis, 2025)
Myasthenic crisis is a severe acute complication of myasthenia gravis (MG) characterized by respiratory and bulbar muscle insufficiency due to impaired neuromuscular transmission, with pathogenesis involving autoantibodies targeting acetylcholine receptors (AChR), muscle-specific kinase (MuSK), and low-density lipoprotein receptor-related protein 4 (LPR4) that disrupt the integrity of the neuromuscular junction. This review aims to examine the immunobiological mechanisms of myasthenic crisis and explore the potential of modern biotechnological therapies and tropical bioactive compounds as adaptive treatment strategies for tropical populations. A comprehensive literature review was conducted focusing on genetic factors, tropical environmental influences, and advancements in molecular therapies. Genetic factors, including HLA class II and non-HLA genes, interact with tropical environmental conditions such as endemic infections, high temperature, extreme humidity, air pollution, and vitamin D deficiency, potentially exacerbating immune dysregulation and increasing crisis risk. Modern molecular therapies, including rituximab (anti-CD20), eculizumab (anti-C5), and efgartigimod (FcRn inhibitor), have demonstrated efficacy in reducing pathogenic autoantibodies and improving neuromuscular function, while tropical bioactive compounds such as curcumin and andrographolide show potential as adjuvant immunomodulators. Integrating biotechnological approaches with tropical bioprospecting provides a more adaptive and sustainable therapeutic strategy aligned with the biological characteristics of tropical populations. It is recommended that further clinical studies evaluate the safety, optimal dosing, and long-term efficacy of combined biotechnological and bioactive therapies in these populations.